PENGARUH BUDAYA ORGANISASI, MOTIVASI , DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT ITHACA RESOURCES - Mochammad Subagio (JURNAL MITRA MANAJEMEN, 2016)
ABSTRACT The purpose of this researched is to find out how big is the effect oforganization culture to ward motivation, job satisfaction and employee’s jobperformance, especially on the employee’s in the production area. The analyticalunit is the employee’s in production area in mining industry in East Kalimanta. Themore positive someone’s behavior will definitely effect her/his performance, this isproven when the researcher tested the hypothesis that motivation effects the jobsatisfaction and job satisfaction effects the performance. The result of the directeffect on employee’s motivation toward job satisfaction is 1.462,and towardperformance is 0.387, the direct effet job satisfaction toward job performance is0.003, the direct effect organization culture toward job performance is 0.506, thedirect effect organization culture toward motivation is 0.680, the direct effectorganization culture toward job satisfaction is 1.183. Beside, this research result isuseful for the next researchers, as research material in organitional behaviorscience or the same kind of science. Keywords: Performance employee, Organization culture, motivation, jobsatisfaction